Sistem Informasi Pelayanan Gangguan Berbasis Web di PT. Telkom Kabupaten Ogan Komering Ulu - Aprima Zahra.M; Anggraeni Agustin Muris; Abdul Rahman (UNIVED Press, 2023)
Telkom Indonesia is a State-Owned Enterprise (BUMN) in the field of IT services, ICT and telecommunications networks in Indonesia. PT. Telkom Indonesia has a service that can be used for individuals or companies, namely Indihome. Indihome is a network package, an Indihome Fiber package that provides internet services, interactive TV and home telephones. It takes a design data system for troubleshooting services that can be accessed by customers and suitable technicians to support the smooth running of the process, processing of complaint information and corrective action. By using the proposed system correctly, it may be easier to monitor the distribution of complaint information, so as to speed up the repair process. This can also help speed up the presentation of reports that are accurate, timely and relevant so that they can assist management in making decisions. This is intended so that technicians do not face the main obstacles in recording information and monitoring the length of time working on field problems. In order to overcome this problem, we need a design data system service for electrical problems that can be accessed by the appropriate admin to support the smooth running of the process of processing complaint information and corrective action.